Unbalanced translocation der(5;17) resulting in a TP53 loss as recurrent aberration in myelodysplastic syndrome and acute myeloid leukemia with complex karyotype. Issue 6 (19th February 2021) - Warnstorf, Daria; Bawadi, Randa; Schienke, Andrea; Strasser, Renate; Schmidt, Gunnar; Illig, Thomas; Tauscher, Marcel; Thol, Felicitas; Heuser, Michael; Steinemann, Doris; Davenport, Claudia; Schlegelberger, Brigitte; et al.
Abstract: A complex karyotype, detected in myelodysplastic syndrome (MDS) and acute myeloid leukaemia (AML), is associated with a reduced median survival. The most frequent chromosomal aberrations in complex karyotypes are deletions of 5q and 17p harboring the tumor suppressor gene TP53 . The unbalanced translocation der(5;17) involving chromosome 5q and 17p is a recurrent aberration in MDS/AML, resulting in TP53 loss. We analyzed the karyotypes of 178 patients with an unbalanced translocation der(5;17) using fluorescence R−/G‐banding analysis. Whenever possible, fluorescence in situ hybridization (FISH) (n = 138/141), multicolor FISH (n = 8), telomere length measurement (n = 9), targeted DNA sequencing (n = 13), array‐CGH (n = 7) and targeted RNA sequencing (n = 2) were conducted. The der(5;17) aberration was accompanied with loss of genetic material in 7q (53%), −7 (27%), gain of 21q (29%), +8 (17%) and − 18 (16%) and all analyzed patients (n = 13) showed a (likely) pathogenic variant in TP53 . The der(5;17) cohort showed significantly shortened telomeres in comparison to the healthy age‐matched controls ( P  < .05), but there was no significant telomere shortening in comparison to MDS/AML patients with a complex karyotype without der(5;17). No fusion genes resulted from the unbalanced translocation. This study demonstrates that the unbalanced translocation der(5;17) is associated with a biallelic inactivation of TP53 due to a deletion of TP53 in one allele and a pathogenic variant of the second TP53 allele. Since the breakpoints are located within (near‐) heterochromatic regions, alterations of DNA methylation or histone modifications may be involved in the generation of der(5;17).